Sputum cytology: a limited role. Issue 7 (July 1997) - Gledhill, A; Bates, C; Henderson, D; DaCosta, P; Thomas, G
Abstract : AIMS: To determine the cost and sensitivity of sputum cytology in routine use and to determine when sputum cytology is most appropriate. METHODS: A retrospective study, based on all sputum cytology requests received in five histopathology/cytopathology laboratories in Yorkshire from 1 January to 31 December 1993. Cytology findings were correlated with histological diagnosis or clinical outcome, and related to the speciality of the referring clinician. RESULTS: Laboratory practice and performance was similar in all five centres. The average laboratory cost of sputum cytology was 26.93. The mean absolute sensitivity was 36% and the specificity was 99.6%. The majority of specimens was submitted by general physicians or geriatricians. The largest proportion of positive specimens were submitted by chest physicians. CONCLUSIONS: Often sputum cytology is used inappropriately as a screening investigation on, or soon after, admission. In addition, it is used inappropriately before bronchoscopy. Sputum cytology should be limited to individuals in whom a histological diagnosis is desired, but in whom bronchoscopy is inappropriate or unsuccessful.